(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize scientific evidence on the effectiveness of physiotherapy interventions for de Quervain’s tenosynovitis from 2020 to 2025 and to evaluate the role of thumb immobilization splints. Methods and literature overview: A systematic review was conducted following the PRISMA 2020 guidelines. Searches were performed in PubMed and the PEDro to identify randomized controlled trials published between January 2020 and October 2025. Results: Among 30 studies initially identified, 7 met the inclusion criteria. Thumb immobilization splints demonstrated clear effectiveness in reducing pain and improving functional outcomes. Additional physiotherapy modalities, including high-intensity laser therapy, shockwave therapy, paraffin heat therapy, and therapeutic exercise, produced positive results, particularly when combined with splinting. Conclusion: Physiotherapy represents an effective conservative treatment option for de Quervain’s tenosynovitis. Thumb immobilization plays an essential role, and combined therapeutic protocols yield superior outcomes compared with single interventions.